Effects of Epicardial and Endocardial Cardiac Resynchronization Therapy on Coronary Flow: Insights From Wave Intensity Analysis. Issue 12 (17th December 2015) - Claridge, Simon; Chen, Zhong; Jackson, Tom; De Silva, Kalpa; Behar, Jonathan; Sohal, Manav; Webb, Jessica; Hyde, Eoin; Lumley, Matthew; Asrress, Kal; Williams, Rupert; Bostock, Julian; et al.
Abstract : Background: The increase in global coronary flow seen with conventional biventricular pacing is mediated by an increase in the dominant backward expansion wave (BEW). Little is known about the determinants of flow in the left‐sided epicardial coronary arteries beyond this or the effect of endocardial pacing stimulation on coronary physiology. Methods and Results: Eleven patients with a chronically implanted biventricular pacemaker underwent an acute hemodynamic and electrophysiological study. Five of 11 patients also took part in a left ventricular endocardial pacing protocol at the same time. Conventional biventricular pacing, delivered epicardially from the coronary sinus, resulted in a 9% increase in flow (average peak velocity) in the left anterior descending artery (LAD), mediated by a 13% increase in the area under the BEW ( P =0.004). Endocardial pacing resulted in a 27% increase in LAD flow, mediated by a 112% increase in the area under the forward compression wave (FCW) and a 43% increase in the area under the BEW ( P =0.048 and P =0.036, respectively). There were no significant changes in circumflex parameters. Conventional biventricular pacing resulted in homogenization of timing of coronary flow compared with baseline (mean difference in time to peak in the LAD versus circumflex artery: FCW 39 ms [baseline] versus 3 ms [conventional biventricular pacing], P =0.008; BEW 47 ms [baseline] versus 8 ms [conventional biventricular pacing], P =0.004). Conclusions: Epicardial and endocardial pacing result in increased coronary flow in the left anterior descending artery and homogenization of the timing of waves that determine flow in the LAD and the circumflex artery. The increase in both the FCW and the BEW with endocardial pacing may be the result of a more physiological activation pattern than that of epicardial pacing, which resulted in an increase of only the BEW.